SISTEM INFORMASI RUMAH SAKIT DAN LINGKUNGAN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI RSUP SANGLAH DENPASAR - I Putu Bagus Suthanaya (Majalah Ilmiah Widyacakra, 2020)
AbstractThe information system is a data processing for decision making in management, as well asthe working environment within the company should be in line with technologicaldevelopments. Sanglah Hospital implements information systems in the hope of improvingemployee performance. This is the focus of the study authors wanted to measure the impact ofinformation systems and work environments in improving employee performance SanglahHospital in Denpasar, as well as employee performance is not enough just to increaseinformation systems, but can also be done through attention to the working environment ofemployees. The study was conducted at Sanglah Hospital in Denpasar, the independentvariable is the information system (X1) and working environment (X2) the dependent variableis employee performance (Y). The population is a permanent employee in the departmentSanglah totaling 2078 people, according to the sampling technique, number of samples to beused as a respondent is 104 people or 5% of total personnel Sanglah Hospital in Denpasar,To determine the effect of information systems on the performance of employees, How big theinfluence of corporate culture and work environment on employee performance SanglahHospital in Denpasar, simultaneous analysis of the results showed that the regressioncoefficient of 0.342 b1x1 which means that any increase in Information Systems (X1) of 1 unitcan improve employee performance amounted to 0.342 units. B2X2 regression coefficient of0.494 which means that any increase in the Working Environment (X2) is a unit led to anincrease of 0.494 units of employee performance. together increased by one unit then theemployee performance (Y) will be increased by 0.836 (0.342 + 0.494) unit. This shows thatInformation Systems (X1) and the Working Environment (X2) effect on employeeperformance (Y) at Sanglah Hospital in Denpasar.